Responsabilidade socioambiental: conhecimento dos profissionais da saúde sobre o gerenciamento de resíduos no serviço público - Gomes, Adrielle Mendes de Paula [UNESP] (2015)
The control of sanitation of a city does not depend solely the staff of the public cleaning, but also the awareness of the general population. To face up this problem, health professionals should also be concerned with waste generated by their activities, requiring the same conscious positioning and willingness to collaborate in finding solutions. Thus, there was a study in municipalities in the northwest of São Paulo, Brazil, in order to verify the knowledge of the health professionals working in the Basic Health Units on policy and management practices of medical waste (MW). This is a descriptive study of transversal, whose developments were divided into two chapters. To collect data, we used one questionnaire that focused on the profile of professional participants and how to manage and management of RSS. In the first chapter, the sample consisted of 74 Dentists. Chi-square and Fisher exact tests were used to assess the association between waste disposal of knowledge and information on the subject, the level of significance of 1%. Of the total of professionals, 97.3% claim to know what RSS is, but 41.9% did not answer correctly disposing sucking and infected gloves and 20.3% needlestick. With regard to information on the subject, 40.5% did not obtain. In addition, a statistically significant difference (p = 0.0007) between the variables information on and disposal of sharps waste. In the second chapter, comprised the sample 11 dentists, 11 oral health assistants, 25 nurses, 21 nursing technicians and 17 nursing assistants. For analysis, we used the nonparametric Kruskal-Wallis...